First Report of Citrus Black Spot Caused by Phyllosticta citricarpa in Angola - Bassimba, Daniel; Nzambi, N.; Paixao, M.I.S.; Katula, I.G.; Vicent, Antonio (APS Press, 2019)
Citrus is an important subsistence crop in Angola, consumed mainly as fresh fruit. In April 2014, fruit symptoms reminiscent of citrus black spot (CBS) consisting of depressed circular spots of about 5 mm in diameter with a light-brown to gray center and black margins surrounded by green rind tissue were observed on a ‘Valencia’ sweet orange (Citrus sinensis) orchard in Bembe, Uíge Province, Angola, with a disease incidence of 47%. Dark brown pycnidia were present in fruit lesions, which often coalesced forming sunken blemishes. Symptomatic fruits from this orchard were surface disinfected with 0.5% NaOCl for 2 min. Small fragments from lesions were plated onto potato dextrose agar (PDA) amended with 0.5 g of streptomycin sulfate/liter and incubated for 15 days at 23°C in the dark. Fungal colonies were transferred to PDA and oatmeal agar (OA) and incubated for 30 days at 23°C with 12-h photoperiod for morphological examination. Colonies were black with irregular margins in PDA and surrounded by a yellow pigment in OA. Pycnidia in PDA were aggregated, globose, dark brown, and 210 µm in diameter. Conidia were 9 to 12 × 5 to 7 µm, hyaline, aseptate, guttulate, obovoid to ellipsoid with truncate base, a mucoid layer and apical appendage. Pycnidia and conidia in PDA or fruit lesions were morphologically similar to those of Phyllosticta (Wikee et al. 2013). The ITS1-5.8S-ITS2 region, partial TEF1-alpha region, and LSU were amplified and sequenced as per Wikee et al. (2013) from DNA extracted from the single-spore isolate IIA-GC003NA, obtained from a Valencia sweet orange fruit from Bembe (GenBank accession nos. KY457232, MF693404, and MF693405, respectively). The sequences had 100% identity with those of P. citricarpa (McAlpine) van der Aa (synonym Guignardia citricarpa Kiely) epitype strain CBS 127454 (Glienke et al. 2011) (GenBank accession nos. JF343583, JF343604, and KF206306, respectively). Laboratory pathogenicity tests were performed by injecting the albedo of 30 mature detached fruit of Valencia sweet orange with 100 µl of a suspension of 3.0 × 104 conidia/ml of water of the isolate IIA-GC003NA (Perryman et al. 2014). Fruits treated with sterile distilled water were used as controls. Fruits were maintained in humid chambers for 40 days at 24 to 26°C with 12-h photoperiod, and those inoculated with the fungus developed depressed necrotic lesions after 35 days. Field pathogenicity tests were performed on 12- to 14-week-old Valencia sweet orange fruits covered by waxed paper bags. Leaf disks colonized by the fungus were placed onto the rind of 60 fruits (Baldassari et al. 2009). Sterile leaf discs were used as controls. Symptoms of a false melanose-type consisting of dark brown stipplings were observed after 86 days on fruit inoculated in the field. No symptoms were observed on control fruit in either experiment. P. citricarpa, identified as described above, was reisolated from lesions on inoculated fruit in all experiments, but not from control fruit. The disease was verified as CBS caused by P. citricarpa. To our knowledge, this is the first report of CBS, caused by P. citricarpa, in Angola. P. citricarpa is responsible for large economic losses worldwide, so further studies are needed to map its geographic distribution, population structure, and impact in Angola.